Analisis Kredit Dalam Perhatian Khusus Studi Kasus: Kredit Mikro Pt. Pegadaian Area Padang - Muhammad Naufal Bryan; Novya Zulva Riani (Universitas Negeri Padang, 2023)
This study aim to determine; (1) the influence of customer characteristics (2) business characteristics (3) credit characteristics on credit with particular attention to PT. Pegadaian Area Padang. This is because every credit, especially micro, cannot be separated from credit risk. Special mention loans are loans that have problems with payments within ninety days and below, and are measured in percentages of LAR (Loan At Risk). Allowing risky credit can lead to credit status to the next stage, namely NPL (Non-Performing Loan) and this will undoubtedly erode the profits of a financial institution. This study uses Ordinary Least Square assisted by Stata 14 software. The results of this study show (1) customer characteristics with indicators of the number of dependents have a positive and significant influence on credit in special attention (2) business characteristics with indicators of the length of business have a negative influence and significant to credit in special mention (3) credit characteristics with term indicators, have a positive and significant influence on the occurrence of credit in special mention.